Women in sustainable agriculture and food biotechnology : key advances and perspectives on emerging topics - Privalle, Laura S. (Springer, 2017)
This volume describes the contributions made by women scientists to the field of agricultural biotechnology, the most quickly adopted agricultural practice ever adopted. It features the perspectives of women educators, researchers and key stakeholders towards the development, implementation and acceptance of this modern technology. It describes the multiplying contemporary challenges in the field, how women are overcoming technological barriers, and their thoughts on what the future may hold. As sustainable agricultural practices increasingly represent a key option in the drive towards building a greener global community, the scientific, technological and implementation issues covered in this book are vital information for anyone working in environmental engineering. Provides a broad analysis of the science of agriculture, focusing on the contributions of women to the field, from basic research to applied technology Offers insights into hot topics in the field across the life cycle, from genetic engineering to optimization methodologies to safety evaluations and market acceptance Describes the complex global nature of modern agriculture and food production.
Includes index.
Keywords: Sustainable agriculture.; Food -- Biotechnology.; Women in agriculture.; elektronické knihy; electronic books